Stop codon read-through with PTC124 induces palmitoyl-protein thioesterase-1 activity, reduces thioester load and suppresses apoptosis in cultured cells from INCL patients - Sarkar, Chinmoy (2011)
Infantile neuronal ceroid lipofuscinosis (INCL), a lethal hereditary neurodegenerative lysosomal storage disorder, affects mostly children. It is caused by inactivating mutations in the palmitoyl-protein thioesterase-1 (PPT1) gene. Nonsense mutations in a gene generate premature termination codons producing truncated, nonfunctional or deleterious proteins. PPT1 nonsense-mutations account for approximately 31% of INCL patients in the US. Currently, there is no effective treatment for this disease. While aminoglycosides such as gentamycin suppress nonsense mutations, inherent toxicity of aminoglycosides prohibits chronic use in patients. PTC124 is a non-toxic compound that induces ribosomal read-through of premature termination codons. We sought to determine whether PTC124-treatment of cultured cells from INCL patients carrying nonsense mutations in the PPT1 gene would correct PPT1 enzyme-deficiency with beneficial effects. Our results showed that PTC124-treatment of cultured cells from INCL patients carrying PPT1 nonsense-mutations induced PPT1 enzymatic activity in a dose- and time-dependent manner. This low level of PPT1 enzyme activity induced by PTC124 is virtually identical to that induced by gentamycin-treatment. Even though only a modest increase in PPT1 activity was achieved by PTC124-treatment of INCL cells, this treatment reduced the levels of thioester (constituent of ceroid) load. Our results suggest that PTC124-treatment induces PPT1 enzymatic activity in cultured cells from INCL patients carrying PPT1 nonsense-mutations, and this modest enzymatic activity has demonstrable beneficial effects on these cells. The clinical relevance of these effects may be tested in animal models of INCL carrying nonsense mutations in the PPT1 gene.